Pathogenesis and Management of Thrombotic Disease in Myeloproliferative Neoplasms - Arachchillage, Deepa RJ; Laffan, Mike (Seminars in Thrombosis and Hemostasis, 2019)
Chronic myeloproliferative neoplasms (MPN) are characterized by clonal expansion of an abnormal hematopoietic stem/progenitor cell and include polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). Venous thrombosis, often at unusual sites, including splanchnic vein thrombosis and arterial thrombosis, as well as a hemorrhagic tendency and a propensity to transform into myelofibrosis or acute leukemia are common complications in patients with MPNs. The pathogenesis of thrombosis in MPN patients is complex and multifactorial. Disease related factors, such as an increase in blood cell counts (i.e., leukocytosis, erythrocytosis, and thrombocytosis), and more importantly presence of JAK2 mutation can interact with non-disease patient related factors such as age, previous history of thrombotic events, obesity, hypertension, hyperlipidemia, and presence of thrombophilic defects. The overall rate of recurrent thrombosis after venous thromboembolism (VTE) is 6.0 to 6.5 per 100 patient-years in patients with MPN compared to 2.7 to 3.7 per 100 patient-years in patients without MPN, and antithrombotic therapy with vitamin K antagonists (VKAs) is associated with a clear benefit, reducing the incidence of recurrence by 48 to 69%. Life-long oral anticoagulation with VKAs is the cornerstone of the antithrombotic treatment for splanchnic vein thrombosis (SVT). Patients with MPN-related cerebral venous thrombosis (CVT) should also be treated with long-term anticoagulation with VKAs. The role of direct acting oral anticoagulants in patients with thrombosis and MPN is not established and the use of these anticoagulants should be considered on an individual basis according to the risk of recurrent of VTE and bleeding.
Keywords: polycythemia vera; essential thrombocythemia; thrombosis; anticoagulation; antiplatelet treatment